Review: Philo of Alexandria. On the Creation of the Cosmos according to Moses. Introduction, Translation and Commentary - Leonhardt-Balzer, Jutta (The journal of theological studies, 2003)
Philo of Alexandria. On the Creation of the Cosmos according to Moses. Introduction, Translation and Commentary. David T. Runia Pp xviii+443 (Philo of Alexandria Commentary Series, 1) Leiden/Boston/KöIn Brill 2001 90 04 12169 2 € 103/$120